EFFECTIVE WAYS OF ASSESSING STUDENTS’ LANGUAGE SKILLS - Axmedova Kamola Ramziddin Qizi (Western European Studies, 2024)
Assessing students' language skills is essential for effective teaching and learning. This annotation outlines key assessment principles that guide educators in evaluating students' language proficiency across reading, writing, listening, and speaking domains. The principles discussed include alignment with learning objectives, authenticity and relevance of assessments, validity and reliability, utilization of multiple assessment methods, incorporation of formative and summative assessment, establishment of clear criteria and rubrics, consideration of differentiation and inclusivity, provision of timely feedback, and a focus on continuous improvement. By adhering to these principles, educators can create meaningful assessment experiences that support students' language development and contribute to their overall academic success.
Keywords: project-based assessments; rubrics; reliability; rhythm